ANALYTICAL MODELING OF NON PLANAR MOSFET - Endro Suseno, Jatmiko (BERKALA FISIKA, 2012)
The Non Planar MOSFET structure with curved-channel is one alternative MOSFETÂ structure for enhance the electrical performance. The study was focused on the non planar deviceswhich has curved-channel including grooved-gate, recessed-channel, V-shaped and sidewallvertical MOSFET. The presence of corner region can effective in reducing the electric field at thedrain, thus improving reliability of short channel effects (SCEs). The corner effect can reducesurface potential. It can improve the characteristic of the device electrical performance, especiallythe reduction of short channel effect and hot carrier effects. Therefore, the curved-channelMOSFET has a very great application prospect in deep submicron device architecture.Keywords: MOSFET, Non Planar, curve channel, surface potential, short channel effects